Physiological responses of Zostera marina and Cymodocea nodosa to light-limitation stress - Silva, João (2014)
The effects of light-limitation stress were investigated in natural stands of the seagrasses Zostera marina and Cymodocea nodosa in Ria Formosa coastal lagoon, southern Portugal. Three levels of light attenuation were imposed for 3 weeks in two adjacent meadows (2–3 m depth), each dominated by one species. The response of photosynthesis to light was determined with oxygen electrodes. Chlorophylls and carotenoids were determined by high-pressure liquid chromatography (HPLC). Soluble protein, carbohydrates, malondialdehyde and phenol contents were also analysed. Both species showed evident signs of photoacclimation. Their maximum photosynthetic rates were significantly reduced with shading. Ratios between specific light harvesting carotenoids and the epoxidation state of xanthophyll cycle carotenoids revealed significantly higher light harvesting efficiency of C. nodosa, a competitive advantage in a low light environment. The contents of both soluble sugars and starch were considerably lower in Z. marina plants, particularly in the rhizomes, decreasing even further with shading. The different carbohydrate energy storage strategies found between the two species clearly favour C. nodosa's resilience to light deprivation, a condition enhanced by its intrinsic arrangement of the pigment pool. On the other hand, Z. marina revealed a lower tolerance to light reduction, mostly due to a less plastic arrangement of the pigment pool and lower carbohydrate storage. Our findings indicate that Z. marina is close to a light-mediated ecophysiological threshold in Ria Formosa.